Addressing discordant quantitative urine buprenorphine and norbuprenorphine levels: Case examples in opioid use disorder. (1st May 2018) - Holt, Stephen R.; Donroe, Joseph H.; Cavallo, Dana A.; Tetrault, Jeanette M.
Highlights: Providers should monitor buprenorphine levels when managing opioid use disorder. Discordant levels should lead to a timely conversation with the patient. A non-judgmental, normalizing approach to addressing urine adulteration is proposed. After urine adulteration, providers should strive to maintain retention in treatment. Abstract: Introduction: Urine adulteration is a concern among patients treated for opioid use disorder. Quantitative urine testing for buprenorphine (B) and norbuprenorphine (NB), and the appropriate interpretation of B and NB levels, can facilitate constructive conversations with patients that may lead to modifications in the treatment plan, and strengthening of the patient-provider relationship. Case summary: Three cases are presented in which discordant urine B and NB levels were recognized. Each patient was submerging buprenorphine/naloxone strips in their urine to mask ongoing illicit drug use. The authors used an approach to addressing intentional adulteration of urine samples that adheres to the principles of harm-reduction, the centrality of the patient-provider relationship, and the acknowledgment that ongoing illicit drug use and subsequent dishonesty about disclosure may be common among persons with substance use disorders. Each of the three patients ultimately endorsed diluting their urine, which allowed for strengthening of the patient-provider relationship and modifications to their treatment plans. Two of the three patients stabilized and achieved abstinence, while the third was eventually referred to a methadone treatment program. Conclusion: Providers should routinely monitor B and NB levels, rather than qualitative screening alone, and discordant levels should elicit a timely conversation with the patient. The authors use of a nonjudgmental approach to address urine adulteration, including giving patients an opportunity to reflect on potential solutions, has been effective at helping patients and providers to reestablish a therapeutic alliance and maintain retention in treatment.